JENIS DAN POPULASI SERANGGA PADA TANAMAN TOMAT (Lycopersicum esculentum Mill) FASE GENERATIF YANG MENGGUNAKAN PUPUK ORGANIK DAN ANORGANIK DI DESA TONSEWER KECAMATAN TOMPASO II - Selvia D. Sumual; Betsy A.N. Pinaria; Dantje Tarore; Emmy Senewe (Universitas Sam Ratulangi, 2014)
ABSTRACTThe tomato Plant (Lycopersicum esculentum Mill.) is an important horticultural plant and classified as the second most important vegetable after the potato. This research’s purpose is to know what insect species and their populations that are associated to tomatoes in their generative phase, which use organic and non-organic fertilizer, in the village of Tonsewer, Tompaso II district. This research is hoped to give information about the species and population of insects that are associated to tomatoes in their generative phase, which use organic and non-organic fertilizer, and thus become a reference for decisions on controlling. This research was done in fields at Tonsewer village, and insect identification was done in the Entomology Laboratory of Pest and Plant Disease Program. The research was done through surveys and samples were collected by swiping a dragnet in a double swing five times. The result of this research showed that tomato plants using organic fertilizer was associated with 5 insect orders, such as : Hemiptera ; Diptera ; Hymenoptera ; Lepidoptera ; Thysanoptera. Meanwhile, the insects in tomato plants using non-organic fertilizer were classified in 6 orders, such as Hemiptera ; Diptera ; Hymenoptera ; Lepidoptera ; Thysanoptera ; Coleoptera. The highest population of insects in tomato plants using organic fertilizer was Hemiptera (Family Miridae: Nesidiocoris tenuis) with 115 individuals, and the lowest population was Lepidoptera (Family Pyralidae : Diaphania indica), with 2 individuals. The highest population of insects in tomato plants using non-organic fertilizer was Hemiptera (Family Miridae : Nesidiocoris tenuis), with 125 individuals, and the lowest population was Lepidoptera (Family Hesperiidae : Erhionata thrax), with 1 individual.Keyword: tomato plant, organic fertilizer, non-organic fertilizer, insect species, insect population